Measurement of charged particle spectra in deep-inelastic ep scattering at HERA - Alexa, Calin; Buniatyan, Armen; Dodonov, V.; Hennekemper, Eva; Herbst, Michael Clemens; Huber, Florian; Pirumov, Hayk; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2013)
Charged particle production in deep-inelastic ep scattering is measured with the H1 detector at HERA. The kinematic range of the analysis covers low photon virtualities, 5<Q 2<100 GeV2, and small values of Bjorken-x, 10−4<x<10−2. The analysis is performed in the hadronic centre-of-mass system. The charged particle densities are measured as a function of pseudorapidity (η ∗) and transverse momentum (p∗T) in the range 0<η ∗<5 and 0<p∗T<10~GeV in bins of x and Q 2. The data are compared to predictions from different Monte Carlo generators implementing various options for hadronisation and parton evolutions.